Consent to Research in Madagascar: Challenges, Strategies, and Priorities for Future Research - Nouvet, Elysée; Grandjean Lapierre, Simon; Knoblauch, Astrid; Baril, Laurence; Andriamiadanarivo, Andry; Raberahona, Mihaja; Mattern, Chiarella; Donelle, Lorie; Andriantsoa, Jean (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2022)
The ethical conduct of research in any setting hinges on the voluntary and informed consent of research participants. Working towards consent that is truly voluntary and informed, however, is far from straightforward, and requires attention to contextual factors that may complicate achievement of this ideal in specific research settings. This paper is based on Madagascar’s first “Consent complexities in health research in Madagascar” workshop, held in Antananarivo, Madagascar, in October 2018. It identifies a number of challenges encountered by individuals responsible for the conduct or oversight of health research in Madagascar related to informed and voluntary consent. Key challenges identified included: adaptation of consent tools into local dialects and for limited literacy populations; perceived acquiescence of potential participants regardless of actual preference based on cultural norms; perceived time pressures within tight project timelines to collect data as quickly as possible, limited time for consent processes; fears and taboos related to specific research procedures or topics; and, uncertainty about how best to approach and verify the validity of individual consent in contexts where traditional leaders’ influence is conventionally sought out and respected. Potential strategies for responding to each of these challenges are proposed, as are key questions meriting further study.